PMM2-CDG T237M Mutation in a Patient with Cerebral Palsy-Like Phenotypes Reported from South India - N. Sreedevi; N. Swapna; Santosh Maruthy; H.S. Meghavathi; Charles Sylvester (Global Medical Genetics)
Congenital disorder of glycosylation (CDG) is an autosomal recessively inherited disorder. Hypotonia, stroke-like episodes, and peripheral neuropathy are also associated with the condition that typically develops during infancy. The patient, a 12-year-old girl born to healthy consanguineous parents, was diagnosed with cerebral palsy as a child. The affected patient has hypotonia, inadequate speech, strabismus, and developmental delay with mild mental retardation, which are key symptoms of CDG. Whole-exome sequencing (WES) identified the known missense pathogenic variant PMM2 c.710 C > T, p.T237M in the patient coding for the phosphomannomutase 2 (PMM2) confirming molecular testing of CDG. The patient's parents carried heterozygous PMM2 c.710 C > T variants. This study highlights the importance of WES in patients with a developmental disability or other neurological conditions, which is also useful in screening risk factors in couples with infertility or miscarriage issues.